EXPRESSION OF THE HEART (American Journal of Technology and Applied Sciences, 2023)
In this article, the poetry of the young penman Ochilboyev Azizbek's poem "Our heart is not cut out for love" and the image of the world of the lyrical hero, the painful feelings are expressed with an ironic spirit. The poet's poems are distinguished by the breadth of the topic, the diversity of poetic thought and expression.